Kadahilanan, Kaakuhan, and Kaunawaan: Yielding the Unheard Narratives of Student Atheists in a Science High School - Agbulos, Jason; Dalupang, Xander Paul; Martin, Eythan Matthew; Matias, Hannah Ashley; Rivera, Monique Louriz; Galdonez, Dominic Patric (Papanda Publisher, 2024)
Atheist is someone who does not subscribe to the belief in a higher power, making it a somewhat controversial stance due to the prevailing religious practices. Atheists often encounter various challenges, including homophobia, misogyny, and other doctrines preached by the church, within their immediate social circles. Despite these negative experiences, the persistent appeal of atheism, driven by the secular movement, continues to attract individuals. This research delves into the experiences of students attending a science high school who identify as atheists, aiming to collect and analyze their personal narratives. The study adopts a qualitative approach with a focus on phenomenology, emphasizing the participants' stories and lived experiences. Data was gathered through interviews with atheist students from the Philippine Science High School Ilocos Region Campus, conducted both online and in-person, and analyzed using Reflexive Thematic Analysis. The data revealed three major themes: Reasons (kadahilanan), Challenges (kaakuhan), and Understand (kaunawaan). Within the Motivation theme, five subthemes emerged: non-religious upbringing, rational thinking, the rejection of hypocrisy, and resistance to bigotry. Similarly, the Acceptance theme included five subthemes: individuality, open-mindedness, misconceptions, pressure to conform to religious practices, and social antagonization. Finally, the Understand theme encompassed four subthemes: involvement in the atheist movement, forming supportive bonds, dealing with mass religious activities, and addressing curriculum-related issues. Based on the collected data, there is a need to strengthen policies that promote the expression of diverse beliefs, including the practice of atheism.